(untitled) (Pesquisa Odontológica Brasileira, 2003)
A cross-sectional study was carried out to analyze tooth loss resulting from caries in relation to the number of times the extracted tooth had been restored, the type of caries diagnosed (primary or secondary), and socioeconomic indicators of patients from the city of Recife, Brazil. Ten public health centres and ten centres associated with health insurance companies were randomly selected. The size of the sample was calculated using a standard error of 2.5%. A confidence interval of 95% and a 50% prevalence of reasons for extractions were used for calculating the sample. The minimum size of the sample for meeting these requirements was 381 patients. Patients were randomly selected from the list of adults registered at each centre. A total of 410 patients were invited to take part in the study. The response rate was 100%, but 6 patients were excluded due to incompleteness of data in the questionnaire applied. An assessment was made to obtain the number of decayed, missing or filled teeth (DMFT index) and the reasons for extraction. The results showed a highly significant (p < 0.001) relationship between the number of times the tooth indicated for extraction had been restored and the reason for extraction being caries. Furthermore, the majority of teeth extracted due to caries had been restored two or more times. A highly statistically significant association was also observed between one indicator of use of dental services (F/DMFT) and extraction due to caries (p < 0.001). The findings questioned the belief that tooth loss can be prevented in the general population by merely providing restorative treatment.